KNOWLEDGE HISTORY MAPPING OF STUDENTS OF PROSPECTIVE CHEMISTRY TEACHERS TO MOVE TACIT KNOWLEDGE TO ACCOUNTABLE EXPLICIT KNOWLEDGE - Kurroti A’yun (PROSIDING SEMINAR KIMIA, 2015)
Students of prospective chemistry teacher need to be freed from misconceptions hidden in their tacit knowledge by moving it into explicit knowledge. Overcoming misconceptions is conducted by mapping their tacit knowledge through misconceptions detection test supported by assessment of learning styles. The combined tests aim to adjust the program for each student. Once their level and type of misconceptions are detected, the students are given misconceptions therapy by utilizing peer cooperation to fill in explicit knowledgemapping table. The mapping table is in accordance with method and practice of teaching adult learners (andragogy). Andragogy is used as underlying theory of teamwork in completing explicit knowledge mapping table because university students’ learning motivation is different from that of school students’. University students are in transition to adult age who seeks knowledge not only for gaining knowledge but also for implementing it in life after college.